Genome profiling is an efficient tool to avoid the STUMP classification of uterine smooth muscle lesions: a comprehensive array-genomic hybridization analysis of 77 tumors - Croce, Sabrina; Ducoulombier, Agnès; Ribeiro, Agnès; Lesluyes, Tom; Noel, Jean-Christophe; Amant, Frédéric; Guillou, Louis; Stoeckle, Eberhard; Devouassoux-Shisheboran, Mojgan; Penel, Nicolas; Floquet, Anne; Arnould, Laurent; et al. (Modern pathology, 2018)
The diagnosis of a uterine smooth muscle lesion is, in the majority of cases, straightforward. However, in a small number of cases, the morphological criteria used in such lesions cannot differentiate with certainty a benign from a malignant lesion and a diagnosis of smooth muscle tumor with uncertain malignant potential (STUMP) is made. Uterine leiomyosarcomas are often easy to diagnose but it is difficult or even impossible to identify a prognostic factor at the moment of the diagnosis with the exception of the stage. We hypothesize, for uterine smooth muscle lesions, that there is a gradient of genomic complexity that correlates to outcome. We first tested this hypothesis on STUMP lesions in a previous study and demonstrated that this 'gray category' could be split according to genomic index into two groups. A benign group, with a low to moderate alteration rate without recurrence and a malignant group, with a highly rearranged profile akin to uterine leiomyosarcomas. Here, we analyzed a large series of 77 uterine smooth muscle lesions (from 76 patients) morphologically classified as 19 leiomyomas, 14 STUMP and 44 leiomyosarcomas with clinicopathological and genomic correlations. We confirmed that genomic index with a cut-off=10 is a predictor of recurrence (P<0.0001) and with a cut-off=35 is a marker for poor overall survival (P=0.035). For the tumors confined to the uterus, stage as a prognostic factor was not useful in survival prediction. At stage I, among the tumors reclassified as molecular leiomyosarcomas (ie, genomic index ≥10), the poor prognostic markers were: 5p gain (overall survival P=0.0008), genomic index at cut-off=35 (overall survival P=0.0193), 13p loss including RB1 (overall survival P=0.0096) and 17p gain including MYOCD gain (overall survival P=0.0425). Based on these findings (and the feasibility of genomic profiling by array-comparative genomic hybridization), genomic index, 5p and 17p gains prognostic value could be evaluated in future prospective chemotherapy trials.